2021
DOI: 10.1002/anse.202000033
|View full text |Cite
|
Sign up to set email alerts
|

Activatable Chemiluminescent Molecular Probes for Bioimaging and Biosensing

Abstract: Chemiluminescence (CL) is a very promising method for applications in analytic chemistry and biological systems due to the elimination of the external light source, which could reduce autofluorescence interference and improve the signal‐to‐noise ratio (SNR) and tissue penetration depth. The fluorescent dyes, chemiluminescent initiator, and reaction temperature are three crucial factors that determine the chemiluminescence efficiency. Up to now, significant development of chemiluminescence probes has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 108 publications
(258 reference statements)
0
8
0
Order By: Relevance
“…The CL emission spectrum obtained in the different transformations is not related to the chemiexcitation mechanism but simply to the fluorescence spectrum of the reaction product formed in its excited singlet state or the excitation energy acceptor present in the system that receives the excitation energy from the initially formed excited product. In the peroxyoxalate reaction, the CL emission wavelength can be chosen almost at will by the choice of the emission spectrum of the activator used, which is chemiexcited by interaction with the high-energy intermediate formed in the reaction sequence [ 108 , 109 , 110 , 111 , 112 ].…”
Section: General Chemiexcitation Mechanismsmentioning
confidence: 99%
“…The CL emission spectrum obtained in the different transformations is not related to the chemiexcitation mechanism but simply to the fluorescence spectrum of the reaction product formed in its excited singlet state or the excitation energy acceptor present in the system that receives the excitation energy from the initially formed excited product. In the peroxyoxalate reaction, the CL emission wavelength can be chosen almost at will by the choice of the emission spectrum of the activator used, which is chemiexcited by interaction with the high-energy intermediate formed in the reaction sequence [ 108 , 109 , 110 , 111 , 112 ].…”
Section: General Chemiexcitation Mechanismsmentioning
confidence: 99%
“…However, due to the limited penetration depth and the autofluorescence of biological tissues, fluorescence imaging encounters a lot of difficulties in deep tissues. Although several red and near-infrared (NIR) fluorescence probes have been commonly explored to enhance the penetration depth, the need for external excitation light source still limits the application of some fluorescence agents in complex deep tissues. Photodynamic therapy (PDT), as a promising cancer treatment strategy, contains three key elements: photosensitizer, light source, and molecular oxygen . Similar to fluorescence imaging, the requirement of an external excitation light source and the limited penetration depth of light retard PDT for diseases in deep tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, the Schaap group reported that certain analytes could specifically trigger 1,2-dioxetanes bearing a phenol functional group to emit strong chemiluminescence, highlighting the great potential as a versatile chemiluminescent platform for detecting a range of biological analytes of interest (Figure b). Since 2015, the Lippert, Shabat, and Pu groups have made many useful modifications to Schaap’s dioxetanes, significantly augmenting the biological applications of dioxetane-type CPs. The introduction of a fluorophore moiety onto the phenol moiety of the adamantyl dioxetane core structure resulted in the first dioxetane-based bioimaging without the requirement of additives . To further improve the properties of these probes under physiological conditions, the Shabat group incorporated an electron-withdrawing methyl acrylate group into the phenol moiety, leading to a significant increase in red-shifted emission wavelengths and chemiluminescence intensity .…”
Section: Introductionmentioning
confidence: 99%